Забезпечення спроможності територіальних громад в Україні - Васильєва, Олександра Іллівна; Бойко, Олена Петрівна (Хмельницький університет управління та права імені Леоніда Юзькова, 2022)
Досліджено сутність поняття спроможності територіальних громад в Україні в умовах реформування місцевого самоврядування. Зазначено, що одним із головних завдань органів місцевого самоврядування в умовах реформування місцевого самоврядування є посилення спроможності територіальної громади, яка здатна гарантувати дотримання прав та інтересів її мешканців, а також їхній захист. Доведено, що зміцнення спроможності територіальних громад є процесом підвищення здатності органів місцевого самоврядування діяти в межах закону, втілюючи в життя принцип верховенства права. Отримання об’єднаними територіальними громадами більше повноважень та ресурсів на їх виконання, а водночас — і відповідальності, повинно стати головним результатом реформи децентралізації в Україні. Саме тому сьогодні забезпечення спроможності територіальних громад є актуальною метою як жителів територіальних громад, так і органів місцевого самоврядування. Зауважено, що територіальна громада як адміністративно-територіальна одиниця базового рівня є цілісністю складників: територіально-природного, демографічного, економіко-господарського, соціального та культурно-ментального, — тому і створюється за критеріями історичної визначеності та соціально-економічної доцільності. Доведено, що спроможність територіальної громади — це наявність бюджетно-фінансових, ресурсних, інфраструктурних та кадрових умов, які визначають здатність територіальної громади надавати якісні публічні послуги населенню, а також можливість задіяти власний потенціал — управлінський, фінансовий, економічний, інвестиційний, людський, громадської участі. Зазначено, що цей напрям дослідження в умовах реформування місцевого самоврядування залишається надзвичайно актуальним для подальших наукових пошуків.

The essence of the concept of the capacity of territorial communities in Ukraine in the context of local self-government reform is investigated. It is noted that one of the main tasks of local government bodies in the context of local government reform is to strengthen the capacity of the territorial community, which is able to guarantee compliance with the rights and interests of its residents, as well as their protection. It has been proven that strengthening the capacity of territorial communities is the process of increasing the ability of local governments to act within the law, implementing the principle of the rule of law. The main result of the decentralization reform in Ukraine should be that the united territorial communities receive more powers and resources to implement them, and at the same time, responsibility. The main result of the decentralization reform in Ukraine should be that the united territorial communities receive more powers and resources to implement them, and at the same time, responsibility. That is why today ensuring the capacity of territorial communities is a relevant goal for both residents of territorial communities and local government bodies. It is noted that a territorial community as an administrative-territorial unit of the basic level is the integrity of the components: territorial-natural, demographic, economic-economic, social, and cultural-mental, and therefore is created according to the criteria of historical certainty and socio-economic feasibility. It has been proven that the capacity of a territorial community is the availability of budgetary, financial, resource, infrastructure and personnel conditions that determine the ability of a territorial community to provide quality public services to the population, as well as the opportunity to use one's own potential - managerial, financial, economic, investment, human, and public participation. It is noted that this direct research in the context of local government reform remains extremely relevant for further scientific research.
Keywords: територіальна громада; органи місцевого самоврядування; спроможність територіальних громад; реформа місцевого самоврядування; territorial community; local self-government bodies; capacity of territorial communities; local self-government reform